Journal of Business Strategy, Finance and Management 2022
DOI: 10.12944/jbsfm.04.01.04
|View full text |Cite
|
Sign up to set email alerts
|

New Energy Vehicles from the Perspective of Market and Environment

Abstract: New energy vehicles have received extensive attention from consumers in today's society. In recent years, the strong rise of pure electric vehicles and hybrid vehicles has brought considerable changes to the entire automotive market. This research mainly focuses on the theme of new energy vehicles and explores the competitive advantages and challenges of new energy vehicles for traditional vehicles from both market and environmental perspectives. This research adopts the method of secondary research, collects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…After 2009, the Chinese and American governments invested in energy development, including new energy such as wind, hydro, and solar energy, and crude oil became irreplaceable [4]. In 2014, China emphasized an inspection in Shanghai, which showcased the development of new energy vehicles [5]. Unlike traditional vehicles, new energy vehicles use electricity as their source of energy, and their combustion emits gases that do not harm the environment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…After 2009, the Chinese and American governments invested in energy development, including new energy such as wind, hydro, and solar energy, and crude oil became irreplaceable [4]. In 2014, China emphasized an inspection in Shanghai, which showcased the development of new energy vehicles [5]. Unlike traditional vehicles, new energy vehicles use electricity as their source of energy, and their combustion emits gases that do not harm the environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unlike traditional vehicles, new energy vehicles use electricity as their source of energy, and their combustion emits gases that do not harm the environment. Analysis of some new energy vehicle companies revealed that overall sales began to grow significantly from 2016 [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e variation of the input error e c , the linguistic variables are taken as E C , the fuzzy domain is bigger negative, smaller negative, zero, smaller positive, and bigger positive (abbreviated as {NB, NS, ZE, PS, PB}), the basic domain is [−60, 60], the discrete domain is taken as [−3, 3], and the quantization factor is taken as 1/20. e output quantity step s, the linguistic variables are taken as S. e fuzzy domains are small, relatively small, medium, relatively big, and big (abbreviated as {S, RS, M, RB, B}), the basic domain is [10,50], and the discrete domain is [1,5]. e quantization factor is 1/10.…”
Section: Fuzzy Control Of Thementioning
confidence: 99%
“…As environmental problems become increasingly serious, new energy vehicles powered by electricity are gradually taking over the market [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, the US Department of Energy [2] highlights the environmental advantages of electric vehicles and their role in diminishing reliance on fossil fuels. Hasan and Islam [3] provide an in-depth analysis of NEVs from both market and environmental standpoints, examining market trends and environmental impacts. While prior studies have explored the market potential and environmental benefits of NEVs, this investigation employs sophisticated analytical methods, such as ridge regression and K-nearest neighbors (KNN), to furnish a more comprehensive outlook.…”
Section: Introductionmentioning
confidence: 99%